Process of the preparation radiopharmaceutical "Nanocolloid 99mTc-Al2O3" for lymphoscintigraphy; International Conference "Nuclear science and its application", Samarkand, Uzbekistan, September 25-28, 2012 : book of abstracts - Nesterov E. A. Evgeny Alexandrovich; Skuridin V. S. Viktor Sergeyevich; Stasyuk (Stasiuk) E. S. Elena Sergeyevna; Varlamova N. V. Natalya Valeryevna; Sadkin V. L. Vladimir Leonidovich; Rogov A. S. Alexander Sergeyevich (2012, 2012)
В фонде НТБ ТПУ отсутствует